Lack of Postprandial Peak in Brain-Derived Neurotrophic Factor in Adults with Prader-Willi Syndrome - Bueno, Marta (PLoS One, 2016)
CONTEXT: Prader-Willi syndrome (PWS) is characterized by severe hyperphagia. Brain-derived neurotrophic factor (BDNF) and leptin are reciprocally involved in energy homeostasis. OBJECTIVES: To analyze the role of BDNF and leptin in satiety in genetic subtypes of PWS. DESIGN: Experimental study. SETTING: University hospital. SUBJECTS: 90 adults: 30 PWS patients; 30 age-sex-BMI-matched obese controls; and 30 age-sex-matched lean controls. INTERVENTIONS: Subjects ingested a liquid meal after fasting ≥10 hours. MAIN OUTCOME MEASURES: Leptin and BDNF levels in plasma extracted before ingestion and 30’, 60’, and 120’ after ingestion. Hunger, measured on a 100-point visual analogue scale before ingestion and 60’ and 120’ after ingestion. RESULTS: Fasting BDNF levels were lower in PWS than in controls (p = 0.05). Postprandially, PWS patients showed only a truncated early peak in BDNF, and their BDNF levels at 60' and 120' were lower compared with lean controls (p<0.05). Leptin was higher in PWS patients than in controls at all time points (p<0.001). PWS patients were hungrier than controls before and after eating. The probability of being hungry was associated with baseline BDNF levels: every 50-unit increment in BDNF decreased the odds of being hungry by 22% (OR: 0.78, 95%CI: 0.65–0.94). In uniparental disomy, the odds of being hungry decreased by 66% (OR: 0.34, 90%CI: 0.13–0.9). Postprandial leptin patterns did no differ among genetic subtypes. CONCLUSIONS: Low baseline BDNF levels and lack of postprandial peak may contribute to persistent hunger after meals. Uniparental disomy is the genetic subtype of PWS least affected by these factors.